Problematika Penyelesaian Sengketa Proses Pemilihan Kepala Daerah Walikota Batam Tahun 2024 di Mahkamah Konsitusi Indonesia - Sabar Sabar; Emy Hajar Abra; Alwan Hadiyanto (Universitas Semarang, 2025)
This study aims to analyze the problems in resolving the 2024 Batam Regional Head Election (Pilkada) disputes at the Constitutional Court of Indonesia. The background of this research lies in the increasing number of electoral disputes that burden the Court, with an urgency to assess whether the existing mechanism can ensure electoral justice. The findings reveal novelty in two critical aspects: first, the identification of inconsistencies between posita and petitum in the petition, which undermines the principle of legal certainty; and second, the urgency of establishing a special electoral court as a structural solution to the Constitutional Court’s heavy caseload. The study concludes that the practice of dispute resolution in the Court still faces a gap between constitutional norms and factual realities. Practical recommendations include revising the Constitutional Court Regulation (PMK) to set stricter standards for petitions and providing continuous electoral legal education for candidates and their legal counsels to strengthen legal certainty and substantive justice. Penelitian ini bertujuan untuk menganalisis problematika penyelesaian sengketa Pemilihan Kepala Daerah (Pilkada) Batam tahun 2024 di Mahkamah Konstitusi. Latar belakang penelitian didasarkan pada tingginya eskalasi sengketa hasil Pilkada di Indonesia yang membebani MK, dengan urgensi menilai sejauh mana mekanisme penyelesaian sengketa mampu mewujudkan keadilan elektoral. Hasil penelitian menunjukkan adanya kebaruan pada dua aspek penting: pertama, identifikasi inkonsistensi antara posita dan petitum dalam permohonan yang berimplikasi pada asas kepastian hukum; kedua, perlunya pembentukan peradilan khusus pemilu sebagai solusi struktural terhadap beban perkara yang terus meningkat di MK. Penelitian ini menyimpulkan bahwa praktik penyelesaian sengketa di MK masih menghadapi kesenjangan antara norma konstitusi dan realitas faktual. Rekomendasi yang diberikan adalah perlunya revisi Peraturan Mahkamah Konstitusi (PMK) agar lebih tegas mengatur standar permohonan, serta penyelenggaraan pendidikan hukum elektoral bagi peserta Pilkada dan kuasa hukumnya guna memperkuat kepastian hukum dan keadilan substantif.